2023
DOI: 10.3390/nu15122726
|View full text |Cite
|
Sign up to set email alerts
|

Standard Hypercaloric, Hyperproteic vs. Leucine-Enriched Oral Supplements in Patients with Cancer-Induced Sarcopenia, a Randomized Clinical Trial

Aura D. Herrera-Martínez,
Soraya León Idougourram,
Concepción Muñoz Jiménez
et al.

Abstract: (1) Background: Malnutrition frequently affects patients with cancer, and it negatively impacts treatment tolerance, clinical outcomes and survival. Thus, appropriate nutritional screening and early nutrition support are extremely recommended. Currently, a significant number of oral supplements (OS) are commercially available; despite this, there is a lack of evidence for recommending specific OS, including leucine-enriched OS, for nutritional support in patients with cancer. (2) Aim: To compare the clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Nutritional support is essential in several human diseases [ 1 ]. Heart failure (HF) is a chronic disease with an increasing incidence (26 million people worldwide), especially in the elderly [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional support is essential in several human diseases [ 1 ]. Heart failure (HF) is a chronic disease with an increasing incidence (26 million people worldwide), especially in the elderly [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…DXA is considered a gold standard for measuring body composition parameters; unfortunately, is not routinely used due to the required logistics, costs, and low-grade radiation exposure [19]. In this context, novel techniques have emerged, such as safe, easy-to-use, and cheap alternatives for measuring body composition parameters [9,[20][21][22]. Among them, electrical bioimpedance analysis (BIA) is probably the most frequently used method.…”
Section: Discussionmentioning
confidence: 99%
“…70 On the other hand, Herrera-Martinez et al compared studies using high-calorie, high-protein, and leucine-rich oral supplements and vitamin D interventions in cancer patients with sarcopenia and found that the muscle mass of patients in the two groups remained stable, with no distinct advantage of leucine observed. 71 Additionally, studies on citrulline supplementation did not show any significant improvement in sarcopenia. 72 Teixeira et al conducted a dietary supplement intervention study on a patient with type 1 diabetes and sarcopenia.…”
Section: Dovepressmentioning
confidence: 97%